Тихий Дон: [роман : в 2 томах] (Михаил Шолохов) - Шолохов Михаил Александрович (Русская классика)
Экземпляры: (20160629) / Инвентарный номер: 49489 / Цена: 641.00 / Авт.знак: Ш 78 / ББК: 84(2Рос=Рус)6-4